Concert and contest collection for C Oboe with piano accompaniment - VOXMAN, H. (Rubank Inc., 1966)
Lagu-lagu untuk oboe:1, Adagio and Allegro - L. Ostransky2. Allegro Moderato (from Trio No. 1 (London) - Haydn-Hervig3. Andante and Allegro(from Sonata in G Major) - Loeillet-Beon4. Aria and Rondinella - G.F. Handel5. Ariette (from Panurge) - Gretrydll